Non-surgical treatment of cervical radiculopathy in outpatient settings. Case report - Aleksei I. Isaikin; Ekaterina K. Kerimova; Kinan Mouki (Consilium Medicum)
Cervical radiculopathy (CR) occurs when the cervical spinal roots are compressed due to degenerative changes in vertebral structures. At the cervical level, compression of radicular structures is most often caused not by the "soft tissue" component of the herniated disc in the epidural space but by compression in the radicular opening itself due to spondylosis. CR can present with various clinical symptoms and their combination in the form of not only pain (usually with "distant" radiation) but also symptoms of dysfunction (hypoaesthesia, motor disorders, decreased tendon reflexes) in the innervation zone of the corresponding spinal roots. Challenge tests aimed at increasing root compression and enhancing clinical symptoms (Spurling, Valsalva, and Elvey tests – Upper Limb Tension Tests, ULTT) are used, as well as other tests to reduce the root compression and relieve pain (traction, shoulder abduction). The diagnosis is based on the analysis of clinical presentation. Root compression is unlikely in the absence of focal neurological symptoms. Native magnetic resonance imaging of the cervical spine is the mainstay of neuroimaging for patients with a new or worsening clinical presentation of non-traumatic CR in the absence of "red flags." When assessing radicular compression, neuroimaging data should be interpreted only in the context of clinical presentation. The presence of anxiety, depression, distress symptoms, and high demands at work is associated with a poor prognosis of recovery and a decrease in the quality of life in patients with CR. Most doctors do not pay enough attention to assessing psychosocial factors. To facilitate this assessment, we have developed a telegram bot. The CR has a naturally favorable course and prognosis. In most cases, CR is a spontaneously resolving condition with a full recovery rate of 83-90%. The method of choice is non-surgical treatment. A case of typical CR is presented. A comprehensive multidisciplinary treatment, including clarification, an educational program, physical therapy, manual therapy, as well as drug therapy (non-steroidal anti-inflammatory drugs, gabapentin, Combilipen) is effective in regression of pain, neurological symptoms, improvement of psycho-emotional status, functional abilities, and quality of life.